Conversor CC-CC trifásico Push-pull de alto ganho alimentado em corrente - Costa, André Elias Lucena da (2018)
This paper presents a new three-phase current-fed Push-Pull DC-DC converter. The proposed converter has reduced size when compared with single-phase topologies and has a simplified gate drive circuit with switches connected to the same reference. When compared with three-phase topologies presented in the literature, the proposed converter has a higher gain and a transformer with reduced leakage inductances, since the voltage applied to the windings has reduced values. A detailed analysis of the converter is presented, containing theoretical waveforms, description of the topological stages and mathematical expressions for the voltages gains and the design of the power structure of the proposed converter with operation in continuous conduction mode and discontinuous conduction mode. In addition, small signal analysis is presented and the converter transfer functions are deduced and validated with simulation results. In order to validate the theoretical analysis simulations are presented and a 700 W prototype was built with an input voltage of 40 V, a output voltage of 400 V and a switching frequency of 40 kHz. With the proposed control strategy, it was possible to maintain the output voltage with at 400 V. The converter had an experimental gain of approximately 10 and is suitable for applications aiming to process the energy from low DC voltage sources.